The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s10853-011-5777-0
|View full text |Cite
|
Sign up to set email alerts
|

Degradation study on ternary zinc magnesium phosphate glasses

Abstract: Glasses with composition (ZnO)30(MgO) x (P2O5)70−x (x = 5, 8, 10, 13, 15, 18, and 20 mol.%) have been successfully prepared by the melt-quenching technique. Degradation study has been carried out by means of measuring their chemical durability against buffer solutions with initial pH values of 4.01, 7.00, and 10.01 at an ambient temperature for up to 30 days. The dissolution rate (D R) was obtained by calculating the measured weight loss of the glasses per unit surface area per unit immersion time. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…This is due to the expected strong ionic cross-linking in the phosphate network structure from the inclusion of Mg 2+ , Zn 2+ and Ca 2+ cations and their respective charge-to-size ratios (0.0232, 0.0227 and 0.0175). The network structure would then be more capable of suppressing the onset of crystallisation in line with previous results [ 20 , 33 , 36 , 37 ]. However, previous studies have also shown that increased network stability is associated with a higher T g due to the increased energy required to fracture the structural bonds that contradicts the comparatively low T g found in these results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is due to the expected strong ionic cross-linking in the phosphate network structure from the inclusion of Mg 2+ , Zn 2+ and Ca 2+ cations and their respective charge-to-size ratios (0.0232, 0.0227 and 0.0175). The network structure would then be more capable of suppressing the onset of crystallisation in line with previous results [ 20 , 33 , 36 , 37 ]. However, previous studies have also shown that increased network stability is associated with a higher T g due to the increased energy required to fracture the structural bonds that contradicts the comparatively low T g found in these results.…”
Section: Discussionsupporting
confidence: 89%
“…However, previous studies have also shown that increased network stability is associated with a higher T g due to the increased energy required to fracture the structural bonds that contradicts the comparatively low T g found in these results. However, this could be accounted for by the general decrease in T g found in ultraphosphate glasses compared to metaphosphate compositions as reported by Ahmed et al [ 12 , 20 , 34 , 37 ]. Based on previous metaphosphate glass compositions studied by Morikawa et al [ 34 ], the large PW may also be attributed to a mixed cation effect between the Mg 2+ and Ca 2+ ions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Franks et al 15) and Lee et al 18) reported that the dissolution rate of MgOCaO Na 2 OP 2 O 5 glasses within the metaphosphate region decreased with increasing the MgO content. Smith et al 20) and Khor et al 17) reported that the chemical durability of MgOZnOP 2 O 5 glasses in near the metaphospate region was improved by increasing the MgO content in the glasses. In our previous work, the chemical durability of CaOP 2 O 5 TiO 2 metaphosphate glasses improved with the addition of MgO, while that of the invert glasses decreased when CaO was substituted by MgO.…”
Section: Discussionmentioning
confidence: 99%
“…However, the introduction of another divalent oxide as MgO has been shown to reduce corrosion rates in aqueous solutions on zinc phosphate glasses [9]. This behavior has been related to some reasons such as the formation of more chemically resistant P-O-Mg bond, or to the decrease of P 2 O 5 content or to the introduction of dual two divalent oxides which can form MO 4 groups and block the pathway for the progress of the process corrosion [10,11].…”
Section: Introductionmentioning
confidence: 99%